Neurotoxicity of drugs of abuse - Slikker, William; Aschner, Michael; Costa, Lucio G. (Advances in neurotoxicology, 2022)
Neurotoxicity of Drugs of Abuse, Volume Eight provides carefully crafted reviews on the disruptive impact of drugs of abuse on the central nervous system. The neurotoxicity potential of several agents including marijuana, fentanyl, and ketamine are carefully reviewed, and their short-term and chronic effects are categorized. Pharmacokinetic profiles as well as mechanisms of action for these and other drugs of abuse such as alcohol and nicotine are also evaluated. The implications of short and long-term abuse for agents such as PCP are also characterized. The reader will come away with a fuller understanding of the adverse effects of drugs of abuse on the nervous system.